Erasmus bilateral agreement for the academic years 2013-2016 Lifelong Learning Programme – Higher Education (Erasmus) between Universidad de Oviedo and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within Socrates programme. - Subject area: Law.